Cystic Fibrosis Transmembrane Conductance Regulator Folding Mutations Reveal Differences in Corrector Efficacy Linked to Increases in Immature Cystic Fibrosis Transmembrane Conductance Regulator Expression - Peters, Kathryn W.; Gong, Xiaoyan; Frizzell, Raymond A. (Frontiers in Physiology, 2021)
Background: Most cystic fibrosis is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene that lead to protein misfolding and degradation by the ubiquitin-proteasome system. Previous studies demonstrated that PIAS4 facilitates the modification of WT and F508del CFTR by SUMO-1, enhancing CFTR biogenesis by slowing immature CFTR degradation and producing increased immature CFTR band B. Methods: We evaluated two correction strategies using misfolding mutants, including the common variant, F508del. We examined the effects on mutant expression of co-expression with PIAS4 (E3 SUMO ligase), and/or the corrector, C18. To study the impact of these correction conditions, we transfected CFBE41o- cells, a bronchial epithelial cell line, with a CFTR mutant plus: a) empty vector; b) empty vector plus overnight 5 µM C18; c) PIAS4, or; d) PIAS4 plus C18. We assessed expression at steady state by immunoblot of CFTR band B, and if present, band C, and the corresponding C:B band ratio. The large PIAS4-induced increase in band B expression allowed us to ask whether C18 could act on the now abundant immature protein to enhance correction above the control level, as reported by the C:B ratio. Results: The data fell into three mutant CFTR categories: a) Intransigent: no observable band C under any condition (i.e. C:B=0); b) Throughput Responsive: a C:B ratio less than control, but suggesting that the increased band C resulted from PIAS4-induced increases in band B production; and c) Folding Responsive: a C:B ratio greater than control, reflecting C18 induced folding greater than that expected from increased throughput due to the PIAS4-induced band B level. Conclusions: These results suggest that the immature forms of CFTR folding intermediates occupy different loci within the energetic/kinetic folding landscape of CFTR. Evaluation of their properties could assist in the development of correctors that can target the more difficult-to-fold mutant conformations that occupy different sites within the CFTR folding pathway.